Zarządzanie zatrudnieniem w szkole wyższej - rozważania modelowe - Wawak, Tadeusz (Management of Employment in a Higher Education Institution - Model Considerations, 2008)
It seems inappropriate to reduce professors employed in an institution of higher education to the institution's resources or personal resources. In order to perform the core university functions (objectives), thе basic functions (objectives) have to be performed first. These basic functions include the employment (personal) function which concerns recruitment, mobility, promoting, dismissal of people employed in a higher education institution and involves management of employment and management of employees. The second part of the publication presents, in a process approach, an original model of the employment management in a higher education institution. The input of the process involves stakeholders, the institution operating conditions, and the divisional structure of the employment management. The main part of the employment management are fields (6), variants of the fields' coordination and the employees. The output involves six segment effects of the employment management and the final effect - quality increase of: labour, education, research, and life. The third part of the publication presents, in a process approach, model of decision making in the fields of employment management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 149-166